A ANALYSIS OF THE EFFECTIVENESS OF ONLINE CUSTOMER REVIEWS AND LIVE STREAMING ON CONSUMER PURCHASE INTEREST ON E-COMMERCE SHOPEE IN KABUPATEN PASAMAN BARAT - Suci Sintia Dewi; Rahmad Saputra; Luis Santos (Yayasan Adra Karima Hubbi, 2026)
This study aims to measure how much the effectiveness of the online customer review and live streaming features in influencing the buying interest of Shopee consumers, especially in Kabupaten Pasaman Barat. The research will be conducted using quantitative methods through a questionnaire survey. The data collected was analyzed using multiple linear regression and processed through the SPSS application. The research findings show that each variable, both online customer reviews and live streaming partially affects the buying interest of Shopee consumers in Kabupaten Pasaman Barat, with a t-count > t-table value, namely 4,302 > 1,68 for online customer reviews, and 4,271 > 1,68 for live streaming. Simultaneously, the two variables are also proven to influence the buying interest of Shopee consumers in Kabupaten Pasaman Barat with an F-count > F-table value, namely 35,596 > 2,80. It is recommended that further research be able to expand the research area and increase the number of research variables. For sellers in Shopee e-commerce, it is advisable to maximize the use of online customer review and live streaming features. For Shopee e- commerce, it is hoped that it will further improve these two features.